Occlusal force, electromyographic activity of masticatory muscles and mandibular flexure of subjects with different facial types (Journal of Applied Oral Science, 2011)
OBJECTIVE: The aim of this study was to evaluate whether vertical facial patterns influence maximal occlusal force (MOF), masticatory muscle electromyographic (EMG) activity, and medial mandibular flexure (MMF). MATERIAL AND METHODS: Seventy-eight dentate subjects were divided into 3 groups by Ricketts's analysis: brachyfacial, mesofacial and dolychofacial. Maximum occlusal force in the molar region was bilaterally measured with a force transducer. The electromyographic activities of the masseter and anterior temporal muscles were recorded during maximal voluntary clenching. Medial mandibular flexure was calculated by subtracting the intermolar distance of maximum opening or protrusion from the distance in the rest position. The data were analyzed using ANOVA followed by Tukey's HSD test. The significance level was set at 5%. RESULTS: Data on maximum occlusal force showed that shorter faces had higher occlusal forces (P